PERLINDUNGAN HUKUM TERHADAP PELAKU NOODWEER DALAM TINDAK PIDANA PEMBUNUHAN - Ekky Saputra; Maryano, Maryano; Hedwig Adianto Mau (Bajang Institute, 2025)
As a manifestation of the principle of the rule of law, every criminal act, referred to in the Indonesian Penal Code (Kitab Undang-Undang Hukum Pidana or KUHP) as a criminal offense (delict), can only be resolved through the applicable legal mechanisms, namely criminal law. An individual may be acquitted of charges if proven not guilty or if the act of violence was committed in self-defense, as regulated under Article 49 of the KUHP, commonly known as